Respuesta :
Answer: [tex]6p^3 + 29p^2 + 22p – 21[/tex]
Step-by-step explanation:
The given expression : [tex](2p + 7)(3p^2 + 4p - 3)[/tex]
To find the product, we need to use the distributive property.
The distributive property is given by :-
[tex]a(b+c)=ab+ac[/tex]
Then , the product will become:
[tex](2p + 7)3p^2 + (2p + 7)4p - (2p + 7)3\\\\=\\\\=(2p*3p^2 + 7*3p^2)+(2p*4p + 7*4p)-(2p*3 + 7*3)\\\\=6p^{2+1}+21p^2+8p^{1+1}+28p-6p-21........\text{Since }a^ma^n=a^{m+n}\\\\=6p^3+21p^2+8p^2+22p-21\\\\=6p^3 + 29p^2 + 22p - 21[/tex]